Circulating corticosterone levels mediate the relationship between acute ethanol intoxication and markers of NF-κB activation in male rats. (1st June 2022) - Barney, Thaddeus M.; Vore, Andrew S.; Trapp, Sarah L.; Finkenberg, Cristal L.; Pugliesi, Dominique R.; Schmalzle, Megha M.; Evans, Shani H.; Varlinskaya, Elena I.; Deak, Terrence
Abstract: Binge drinking is a harmful pattern of alcohol use that is associated with a number of serious health problems. Of particular interest are the rapid alterations in neuroimmune gene expression and the concurrent activation of the hypothalamic-pituitary-adrenal (HPA) axis activation associated with high intensity drinking. Using a rat model of acute binge-like ethanol exposure, the present studies were designed to assess the role of corticosterone (CORT) in ethanol-induced neuroimmune gene expression changes, particularly those associated with the NFκB signaling pathway, including rapid induction of IL-6 and IκBα, and suppression of IL-1β and TNFα gene expression evident after administration of moderate to high doses of ethanol (1.5–3.5 g/kg ip) during intoxication (3 h post-injection). Experiment 1 tested whether inhibition of CORT synthesis with metyrapone and aminoglutethimide (100 mg/kg each, sc) would block ethanol-induced changes in neuroimmune gene expression. Results indicated that rapid alterations in IκBα, IL-1β, and TNFα expression were completely blocked by pretreatment with the glucocorticoid synthesis inhibitors, an effect that was reinstated by co-administration of exogenous CORT (3.75 mg/kg) in Experiment 2. Experiment 3 assessed whether these rapid alterations in neuroimmune gene expression would be evident when rats were challenged with a subthreshold dose of ethanol (1.5 g/kg) in combination with 2.5 mg/kg CORT, which showed limited evidence for additive effects of low-dose CORT combined with a moderate dose of ethanol. Acute inhibition of mineralocorticoid (spironolactone) or glucocorticoid (mifepristone) receptors, alone (Experiment 4) or combined (Experiment 5) had no effect on ethanol-induced changes in neuroimmune gene expression, presumably due to poor CNS penetrance of these drugs. Finally, Experiments 6 and 7 showed that dexamethasone (subcutaneous; a GR agonist) recapitulated effects of ethanol. Overall, we conclude that ethanol-induced CORT synthesis and release is responsible for suppression of IL-1β, TNFα, and induction of IκBα in the hippocampus through GR signaling. Interventions designed to curb these changes may reduce drinking, and subdue detrimental neuroimmune activation induced by ethanol. Highlights: Glucocorticoid synthesis inhibition blocked neuroimmune gene changes induced by high-dose ethanol. Peripheral corticosterone administration reinstated neuroimmune gen changes induced by high-dose ethanol. Ethanol-induced changes in corticosterone likely drive rapid neuroimmune responses in a dose-dependent manner.